How family support alleviates death anxiety in breast cancer patients: the mediating role of meaning in life - Gui, Gui; Yang, Dajun; Liu, Yujie; Yao, Yisong; Xie, Xinling; Liu, Ruining; Liu, Mingye; Liu, Heming; Zhou, Fangfang (Frontiers in Public Health, 2025)
Previous studies have predominantly focused on the relationship between death anxiety and quality of life in breast cancer patients, with limited exploration on how to alleviate their death anxiety. To address this gap, we recruited 533 breast cancer patients and utilized structural equation modeling and Process Model 4 to analyze the internal mechanisms and boundary conditions between family support and death anxiety. The study results indicated that family support significantly negatively impacts death anxiety in breast cancer patients; similarly, meaning in life also significantly negatively impacts death anxiety. More importantly, we found that meaning in life plays a full mediating role between family support and death anxiety. This study suggests that by enhancing family support levels and strengthening patients’ perception of meaning in life, we can significantly improve the psychological health status of breast cancer patients, thereby potentially improving their quality of life.